Pengembangan Asesmen Formatif Berbasis SLOA Pada Materi Statistika Kelas XI SMA - Faizza Zhara Adellia Adi; Chairil Faif Pasani; Rahmita Noorbaiti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2026)
Formative assessment practices in classrooms still focus on final outcomes and have not optimally encouraged students’ learning reflection. This study aimed to develop a valid, practical, and effective SLOA-based formative assessment on statistics of measures of central tendency for single data. The study employed the 4-D development model without the disseminate stage. The trial subjects consisted of 26 students of class XI-12 at SMAN 7 Banjarmasin. The developed product comprised four formative assessment packages in the form of essay questions equipped with self-assessment sheets, scoring rubrics, and answer keys. The results showed that the assessment was categorized as very valid with average scores of 3.57 and 3.75, very practical with 88%, and effective with an average completeness percentage of 88%.